2021
DOI: 10.1088/2634-4386/ac156e
|View full text |Cite
|
Sign up to set email alerts
|

Towards low loss non-volatile phase change materials in mid index waveguides

Abstract: Photonic integrated circuits currently use platform intrinsic thermo-optic and electrooptic effects to implement dynamic functions such as switching, modulation and other processing. Currently, there is a drive to implement field programmable photonic circuits, a need which is only magnified by new neuromorphic and quantum computing applications. The most promising non-volatile photonic components employ phase change materials such as GST and GSST, which had their origin in electronic memory. However, in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…When considering the amorphous (dashed line - R squared = 0.768) the Q-factor remains almost flat ( Q/ = −14.67 ± 3.29 / m), meaning that the impact associated with the PCM loss is very small on the response of the RRs. When considering the crystalline (red line - R squared = 0.793), the Q factor decreases with a steeper rate ( Q/ = / m) when compared to the amorphous , showing higher induced optical loss within the resonant cavity, as also confirmed by previously reported measurements 49 . The average ERs of the resonances in the amorphous state of the PCM is only of 12.5 dB, while in the crystalline state it is 18 dB over the wavelength range centered at = 1.55 m. The extinction ratio and the quality factor depends on the cladding refractive index.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…When considering the amorphous (dashed line - R squared = 0.768) the Q-factor remains almost flat ( Q/ = −14.67 ± 3.29 / m), meaning that the impact associated with the PCM loss is very small on the response of the RRs. When considering the crystalline (red line - R squared = 0.793), the Q factor decreases with a steeper rate ( Q/ = / m) when compared to the amorphous , showing higher induced optical loss within the resonant cavity, as also confirmed by previously reported measurements 49 . The average ERs of the resonances in the amorphous state of the PCM is only of 12.5 dB, while in the crystalline state it is 18 dB over the wavelength range centered at = 1.55 m. The extinction ratio and the quality factor depends on the cladding refractive index.…”
Section: Resultssupporting
confidence: 85%
“…A new family of phase-change materials based on and 46 , 47 has emerged as a promising candidate due to its low absorption in both states at =1.55 m. exhibits a broadband transparency ranging from 0.6 m up to the near-IR, a refractive index contrast ( n) between its states of 0.60 at 1.55 m and low inherent losses with extinction coefficient k values lower than 10 in both phases. Devices such as Bragg gratings 48 , Mach-Zehnder interferometers (MZIs) 49 , Multi-Mode interferometers (MMIs) 50 and ring resonator (RR) modulators on SOI 51 , 52 have recently been demonstrated using these materials.
Figure 1 ( a ) SEM image of a RR design variation with the PCM cell deposited on top.
…”
Section: Introductionmentioning
confidence: 99%
“…(2021) demonstrated that multi-pulse laser irradiation with low pulse energy can improve cycling durability with respect to single-pulse, high-energy irradiation. Despite further studies on the cycles endurance and reversibility of Sb 2 S 3 are needed, integration of Sb 2 S 3 in photonic circuits is already being exploited in the design of Mach–Zehnder interferometers (MZIs) operating in the C and O communication bands ( Faneca et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The low optical loss and the optical phase modulation of Sb 2 S 3 were investigated by Dong et al onto the SiN platform at 750 nm [203], showing the potential of the PCM broadband material together with a silicon nitride platform in applications such as, postfabrication trimming, large-scale integrated quantum photonic networks and optical field-programmable gate arrays (FPGAs) in the visible range of the spectrum. In [207], low-loss PCMs (Sb 2 S 3 and Sb 2 Se 3 ) were integrated with MZI building blocks based on a SiN platform, see Figure 8h, to experimentally demonstrate the advantages of using this platform integrated with PCMs in both the O-and C-bands, in comparison with a SOI platform [208]. This experiment demonstrated a low insertion loss of around 0.04 dB/µm for Sb 2 S 3 -and 0.09 dB/µm for Sb 2 Se 3 -integrated devices in both amorphous and crystalline states.…”
Section: Phase Change Materialsmentioning
confidence: 99%
“…(g) Schematic of low-loss nonvolatile SiN photonic-integrated Bragg grating based on Sb 2 S 3 and GSST; reproduced from [204] under a CC BY 4.0 license. (h) Microscope image of a SiN MZI with a Sb 2 S 3 cell deposited in one of the arms; reproduced from [207] under a CC BY 4.0 license. (i) Schematic of an integrated photonic graphene microheater for phase change chalcogenides on SiN building blocks; reproduced from [215] under a CC BY 4.0 license.…”
Section: Permanent Tuning Of the Refractive Indexmentioning
confidence: 99%